Dermatomyositis and Paclitaxel-Induced Cutaneous Drug Eruption Associated with Metastatic Breast Cancer - Kim, Youngji; Jung, Woojin; Park, Yeon Hee (Journal of breast cancer, 2015)
Dermatomyositis (DM) is an idiopathic autoimmune connective disease characterized by muscles and skin inflammation of and a well-recognized association with several human malignancies, especially breast cancer. Paclitaxel is a taxane antineoplastic agent with therapeutic effects against a wide range of cancers including breast cancer. This drug is well known for neurotoxicity and hypersensitivity reactions. However, cutaneous drug eruptions, especially those of grade III or higher, are not frequent. Here, we describe the case of a 55-year-old woman with metastatic breast cancer who developed paraneoplastic DM and a paclitaxel-induced exanthematous drug eruption. This case report emphasizes the importance of evaluating internal malignancies, such as advanced breast cancer, in newly developed DM patients. In addition, it presents a rare case of paclitaxel-induced exanthematous drug eruption. The purpose of this case report highlights the immunological pathogenic mechanism of DM and drug eruption in underlying advanced breast cancer.